Transformation of Micro Small and Medium Enterprises in Semarang through Implementation of Intellectual Property Rights as an Effort to Implement State Thinking that Happy the People's Law - Yuliandari, Erna; Hendri N, Muhammad; Kharisma, Dona Budi; Anam, Choiroel; Febrianty, Alifia Della (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Small and Medium Enterprises (MSMEs) are the largest economic supporter in Indonesia. Semarang is one of the vast regions in Indonesia and the capital of Central Java Province in this case also has MSMEs with great growth potential. Intellectual property rights are at the heart of the creative economy. Lack of understanding related to the urgency of Intellectual Property Rights can hinder MSMEs from transforming. IPR can make businesses more developed and avoid harmful disputes. This study aims to describe the understanding of MSME entrepreneurs in Semarang about IPR and how to transform MSMEs in Semarang through the Implementation of Wealth Rights. The method used is descriptive qualitative. The instrument used in this study used primary data, namely interviews and questionnaires which were distributed to SMEs in Semarang and also used literature studies. The results of the study show that the understanding of SMEs in Semarang already understands IPR, for business actors IPR is important as a form of legal protection, but there are still many business actors who do not understand how to obtain IPR. Therefore, it is necessary to reaffirm the understanding of the urgency of Intellectual Property Rights and how to obtain Intellectual Property Rights to make MSMEs transform to be more effective and efficient, and independent and the realization of a state of law that makes its people happy.